SCARCITY OF SUBSIDIZED FERTILIZER AND WEATHER FACTORS: IMPLICATIONS FOR AGRICULTURAL PRODUCTIVITY AND FOOD SECURITY IN PROBOLINGGO REGENCY - Achmad Febrianto; Najma Nur Lathiefah (Nurul Jadid University, 2025)
Probolinggo Regency is an agricultural area where the majority of the population works as farmers. However, the agricultural sector in this area faces major challenges due to the scarcity of subsidized fertilizers and unpredictable weather changes. This study aims to analyze the scarcity of subsidized fertilizers and weather factors on agricultural productivity and food security in Probolinggo Regency, as well as to evaluate sharia-based economic solutions that can be applied to improve farmer welfare. The research method used is a qualitative approach with a case study method. Data were collected through in-depth interviews with farmers, fertilizer distributors, and Bulog officials, as well as field observations and documentation studies. The results of the study indicate that the uneven distribution of subsidized fertilizers and high prices of non-subsidized fertilizers cause many farmers to have difficulty meeting their fertilization needs, thus negatively impacting agricultural productivity. In addition, extreme weather changes, such as unpredictable rainfall and prolonged drought periods, worsen agricultural conditions and increase the risk of crop failure. The implications of this problem include declining agricultural production, increasing food prices, and socio-economic instability for farmers. To overcome these challenges, adaptation strategies are needed, such as better management of fertilizer distribution, the use of agricultural technology that is more adaptive to climate change, and the application of sharia economic principles to create a just and sustainable agricultural system.